Implementation of Automatic Transfer Switch on the Solar Home System at the Goat Farm Houses - Chamim, Anna Nur Nazilah; Peggy Irawan, Agil; Syahputra, Ramadoni (Journal of Electrical Technology UMY, 2020)
In Pirak Mertosutan Hamlet, Sleman, Yogyakarta, there is a goat farm complex with about 600 m2. The intricate lighting comes from the National Electricity Company (PLN) and the Solar Home System (SHS). SHS is the primary energy source for lighting, while PLN is a secondary energy source that replaces it when the power supply from SHS goes out. So far, the transfer from SHS to PLN has been carried out by humans. This fact is considered inefficient because the SHS supply does not always die during the day. At night, the officers who move the difficulties have to go to the cage complex located relatively far from residential areas. To facilitate the transfer of energy sources from SHS to PLN and vice versa. It does not need to be done by officers. It is necessary to automatically install a means to automatically move the two sources automatically. This tool is the Automatic Transfer Switch (ATS). This tool can move the energy supply from SHS to PLN and vice versa. By considering the specifications used in the SHS in the farm complex, the ATS is made and then installed in the farm complex. After the installation is carried out, the functional test is carried out. The ATS installation test results show that the ATS can work according to the design; namely, when the SHS is off, the source used is automatically switched to PLN. When the SHS is on, the source that was using PLN will automatically switch to SHS.